Implementasi Pemenuhan Hak Anak dalam Mewujudkan Kota Layak Anak di Kota Samarinda: Content Variable Analysis - Ema Karisma Wati; Fajar Apriani (Syntax Corporation Indonesia, 2024)
In order to realize a Child Friendly City, the Samarinda City Government implementing the Fulfillment of Children’s Rights program. This research aims to determine the implementation of the fulfillment of children’s rights carried out by the Samarinda City Women’s Empowerment and Child Protection Service, on policy content variables based on the theory of policy implementation model from Grindle which consist of six elements, namely the interest affected by the policy, the types of benefits generated, the degree of change that occurs, the position of policy makers, program implementers and the resources mobilized. By using a qualitative descriptive research approach, this research concludes that the implementation of Child Friendly Regency/City in Samarinda City based on the contents of its policies has achieved good results with obtained the Nindya level of Child Friendly City award through involving various cross-sectoral stakeholders and placing children as “Pioneers and Reporters” in involvement in the Children’s Forum. The Samarinda City Child Friendly City program has become a pilot area for other regions in East Kalimantan Province. However, the comprehensive fulfillment of children’s rights has still not been achieved, especially for children in the street, homeless, beggars and children who have been married early. There is a need for cooperation between the Samarinda City Women’s Empowerment and Child Protection Service and the Social Service that is more progressive in handling these children’s cases to fulfill their rights better.